Intra-urban and peri-urban differences in cattle farming systems of Burkina Faso. (November 2015) - Dossa, Luc Hippolyte; Sangaré, Mamadou; Buerkert, Andreas; Schlecht, Eva
Highlights: We determined the differences between intra-urban and peri-urban cattle farming systems. 5 Intra-urban and 4 periurban farming systems were identified. Intra-urban systems were oriented towards beef production and peri-urban towards milk. Intensive landless fattening systems seem the most promising in the intra-urban area. Small dairy herds seem the most adapted to continuously changing peri-urban environment. Abstract: Little is known about the classification of urban and peri-urban cattle farming systems in West Africa. To contribute to filling this knowledge gap, we conducted a questionnaire-based survey in 137 and 133 cattle enterprises located, respectively, within and beyond the municipal boundaries of the city of Bobo Dioulasso in Burkina Faso. Categorical principal component and two-step cluster analysis techniques were used to group the different farms. The farmer's engagement in crop production, the area of cultivated land, his experience in cattle farming, the orientation of the cattle enterprises towards fattening or milk production and the feeding mode (zero-grazing, grazing only or grazing plus supplementation), among others, were relevant differentiating factors. Overall nine distinct clusters reflecting different farming systems in the intra-urban and peri-urban areas were identified. Farm types in the intra-urban area were mainly oriented towards meat production and included intensive landless cattle fattening ( n  = 30; 21.9%), semi-intensive grassland-based cattle farming ( n  = 40; 29.2%), extensive cattle farming ( n  = 20, 14.6%), semi-intensive maize-cattle farming ( n  = 37, 27.0%) and intensive maize-cattle farming ( n  = 10, 7.3%). In contrast, farms in the peri-urban area were mostly oriented towards milk production and classified as semi-intensive pastoral ( n  = 11; 8.3%), semi-sedentary pastoral ( n  = 38; 28.6%), medium-scale agro-pastoral maize-dairy farming ( n  = 40, 30.1%), and small-scale agro-pastoral dairy-maize farming ( n  = 44; 33.1%). The intensive landless fattening enterprises seem to be most promising for the future exploitation of the growing demand of urban customers for beef, whereas small dairy herds integrated or not with crop production appear to be the most adapted to the continuously changing peri-urban environment.